Malāmiḥu al-Itijāhi al-Maqaṣidi fi al-Tafsir: al-Kulyāt al-Khamsa fi al-Tafsir al-Rāzi Namudhjan - Khan, Israr Ahamd; Khan, Musaddiq Majid (Faculty of Islamic Revealed Knowledge and hHman Sciences (IRKHS), International Islamic University, Malaysia., 2011)
This research dealt with the concept of the theory of the objectives of Shariah and its application in Tafsīr Kabir of Imam of Al-RaÌi, through the study of the five universals: religion, self, mind, progeny, and property. The research refutes the assumption of some people who think that Razi claims, “the commandments of God no rationale at all and so are his actions”. So they built on this assumption another claim that Razi rejects the theory of objectives, when in fact it is not so, as to be seen in the examples provided in this research. The research finds that Razi provides the rationale of the Qur’Énic verses and mentions their objectives while tackling interpretation from time to time.